2019
DOI: 10.1136/bmj.l877
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy and cognition

Abstract: Evidence is reassuring for women needing a few years’ treatment for menopausal symptoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In this regard, several research studies on interventions aimed at hormone replacement have been conducted. In some cases, hormone supplementation (or HRT, Hormone Replacement Therapy) with estradiol has generated enormous interest for its potentially beneficial effects ( 36 , 37 ). Specifically, menopause-related obesity and loss of lean and skeletal muscle mass have been shown to reverse following estradiol hormone therapy ( 38 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In this regard, several research studies on interventions aimed at hormone replacement have been conducted. In some cases, hormone supplementation (or HRT, Hormone Replacement Therapy) with estradiol has generated enormous interest for its potentially beneficial effects ( 36 , 37 ). Specifically, menopause-related obesity and loss of lean and skeletal muscle mass have been shown to reverse following estradiol hormone therapy ( 38 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Nevertheless, a recent review has suggested that OVX results in a “blank ovarian hormone state,” which is an ideal model to evaluate the effects of ovarian hormone deprivation and the outcomes of subsequent exogenous hormone treatments on the brain (Koebele and Bimonte-Nelson, 2016 ). Indeed, epidemiological data regarding women who underwent OVX before the onset of natural menopause indicate a long-term increased risk of AD (Rocca et al, 2010 ) and furthermore ERT efficacy is similar in both natural menopause and oophorectomy in women, depending on the timing of treatment initiation (Mosconi et al, 2004 ; Maki et al, 2019 ). Given that female mice continue to experience hormonal cycles with age (Hung et al, 2003 ), the use of OVX can be considered an effective model to mimic human/primate menopause in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of HRT use may be crucial, such that there is a critical window which exogenous hormone use can confer cognitive bene ts in postmenopausal women. 29,40 Strengths and limitations…”
Section: Exogenous Hormone Usementioning
confidence: 99%